Galectin-3 and soluble ST2 as complementary tools to cardiac MRI for sudden cardiac death risk stratification in heart failure: A review. (September 2020) - Shah, Niel N; Ayyadurai, Puvanalingam; Saad, Muhammad; Kosmas, Constantine E; Dogar, Muhammad U; Patel, Upen; Vittorio, Timothy J
Heart failure (HF) is recognized as one of the leading causes of morbidity and mortality worldwide. Every year about 500, 000 new cases of HF are diagnosed in the United States. The predominant etiology of death in HF patients include sudden cardiac death (SCD) and pump failure. Prediction of mode of death may help in devising management decisions. In patients with HF, the presence of myocardial fibrosis has been a known risk factor for SCD and thus it could be used as a criterion in risk stratification for SCD. However, the underlying pathophysiology of SCD is uncertain and controversial, which makes it necessary to develop newer tools to enhance SCD risk stratification. The newer tools should be innovative enough either to complement or to replace the currently available tools. In this scoping review, we highlighted the utilization of novel biomarkers galectin-3 (gal-3) and soluble ST2 (sST2) and discussed that how they might complement currently available tools such as, cardiac MRI (CMR) for SCD risk stratification in HF patients.